AUTOCRATIC LEGALISM AND THE DECLINE OF CONSTITUTIONAL COURT AUTONOMY IN INDONESIA - Muhammad Anugerah Perdana (KANUN:JURNAL ILMU HUKUM, 2025)
The consolidation of a dominant parliamentary–executive coalition in Indonesia from 2017 to 2022 illustrates how a populist democratic government can gradually drift toward authoritarianism. This shift has weakened institutional autonomy and contributed to a series of controversial judicial rulings on contested statutes during formal review in the Constitutional Court, including the Job Creation Law, the Constitutional Court Law itself, and the Mineral and Coal Law. This study examines how vulnerable Constitutional Court independence remains in the face of autocratic legalism concerning these laws. Employing a normative juridical method with a casuistic and comparative approach, and drawing on the experiences of Poland and Hungary, the paper evaluates the resilience of Constitutional Court independence under authoritarian legalism and its implications for Indonesia’s evolving constitutional order. This transformation did not occur through overt illegality but through legal deviations that strategically exploit loopholes within the constitutional framework. Autocratic legalism rests on three features: (1) the co-optation of parliamentary power by the ruling coalition, (2) violations of statutory and constitutional norms, and (3) the erosion of judicial independence. The third feature became evident following the enactment of Law No. 7 of 2020 on the Third Amendment to the Constitutional Court Law. The ratification of this legislation represented a calculated attempt by Parliament to constrain the Court, concealed within an extension of judicial tenure. This development poses a significant challenge to democracy and justice in Indonesia in the years to come